Uma análise da lista suja no Maranhão como ação de repressão do trabalho escravo - Araújo, Bruna Feitosa Serra de (2017)
The present research has as its scope the analysis of the Dirty List in the State of Maranhão as an action to repress slave labor. The historical context of neo-slavery and its normative repercussions are analyzed, through the recognition of the problem in the Inter-American Court of Human Rights and the regulatory framework at the international, national and state levels. Maranhão is present in the contemporary representation of slavery. It is observed that victimization for slave labor is linked to the cultural roots that for centuries tolerate this type of exploitation, together with impunity, lack of professional qualification and geographic isolation that favor this type of behavior in certain regions of the state. The (in) constitutionality of the Dirty List is considered in the light of the Federal Supreme Court, which in its decisions now prohibits, and authorizes its publication.